Samos Syndrome, Women with Borderline Personality Disorder and Risk for Sexually Transmitted Infections and HIV: Their Role During Pandemics - Lazzari , Carlo (Current Innovations in Disease and Health Research Vol. 7, 2023)
The author (CL) discovered the Samos Syndrome when researchers investigated why certain people refuse to take precautionary measures even when aware of pandemic risks. Samos Syndrome suggests that pandemic and primary prevention can only occur if people care about staying healthy and avoiding communicable illnesses. When faced with risky transmissible diseases, individuals either defend themselves or welcome them. This last is what happens in Samos Syndrome. The syndrome is a kind of pathophilia (people attracted by illnesses). As borderline personality disorder, found in Samos Syndrome, becomes more common, so will people who reject primary protection from infectious diseases and health behaviour as their choice. Therefore, we cannot halt pandemic outbursts. Pandemics would sinisterly draw pathophilies and split individuals who wish to avoid sickness from others who would surf the risk caused by pandemics to harm themselves for personal, interpersonal, and psychological reasons.